The Effect of Human Development Index, Inflation and Economic Growth on Unemployment in Medan City - Inda Arfa Syera; Adetia Azmi Tanjung; Windi Triana (International Journal of Economics (IJEC), 2023)
The purpose of this study was to determine the effect of the human development index, inflation and economic growth on unemployment in the city of Medan. The approach used in this research is a quantitative approach. The data used in this study are secondary data sourced from the Central Bureau of Statistics for the City of Medan with the data period from 2003 to 2022. The analysis technique used is the classical assumption test (normality test, multicollinearity test, heteroscedasticity test and autocorrelation tests). multiple linear regression, and hypothesis testing (statistical F test, and statistical t test, and test of the coefficient of determination (R2)). The results of this study are based on the results of the simultaneous test (f test) it can be seen that the variables human development index, inflation and economic growth are significant together (simultaneously) on the Unemployment variable. Based on the partial test of the Human Development Index variable, it has a negative and significant effect on Unemployment in Medan City, the Inflation variable has a negative and insignificant effect on Unemployment in Medan City and the Economic Growth variable has no effect on Unemployment in Medan City.